1977
DOI: 10.1203/00006450-197704000-00215
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin Synthesis in Human Embryonic and Fetal Tissues

Abstract: & Ob-Gyn & . ; *sear ch CenLe:. Moffett Field. Ca. The fetus appears t o be capable o f homeostatic regulation o f i t s f l u i d environment i n utero. Possible hormonal modulation mechanisms influencing cardiovascular homeostasis include AVP. which i n a d u l t animals i s released from the posterior p i t u i t a r y i n response t o hyperosmolar s t i m u l i o r volume depletion. Fetal AVP production was studied i n chronically prepared unstressed fetuses and i n acutely hemorrhaged fetuses from 0.4 o f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1981
1981
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Gitlin et al (4) reported that among macromolecules in the serum of mothers they studied, only IgG could pass the placenta into the cord serum with a concentration increasing to reach that in the maternal serum toward birth. The other molecules such as albumin, transferrin and IgM did not pass the placenta appreciably.…”
Section: Discussionmentioning
confidence: 99%
“…Gitlin et al (4) reported that among macromolecules in the serum of mothers they studied, only IgG could pass the placenta into the cord serum with a concentration increasing to reach that in the maternal serum toward birth. The other molecules such as albumin, transferrin and IgM did not pass the placenta appreciably.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon the high specific activity of IgM antibodies as compared with IgG antibodies in several biologic assays. including complement-dependent bactericidal reaction and opsonization and protection tests, several investigators proposed that the deficiency of this immunoglobulin in the newborn was related to increased susceptibility of infants to gram-negative infections (12). In addition, other developmental deficiencies, such as diminished serum complement proteins.…”
Section: Neonatal E Coli Meningitismentioning
confidence: 99%
“…a-Fetoprotein (AFP) and serum albumin are major plasma proteins both synthesized in mammalian liver parenchymal cells. AFP is also produced in the embryonic yolk sac (1) and is a single chain glycoprotein with a molecular weight of70,000 containing 4% carbohydrate (2)(3)(4)(5)(6). AFP synthesis is associated with developmental and neoplastic processes (7)(8)(9), and it is the dominant plasma protein of the mammalian fetus.…”
mentioning
confidence: 99%